Jim Mansell y Julie Beadle-Brown (2012): Active Support. Enabling and empowering people with intellectual disabilities. Londres: Jessica Kingsley Publishers. - Tania Cuervo Rodríguez (Revista Española de Discapacidad, 2016)
Reseña de la obra 'Active Support. Enabling and empowering people with intellectual disabilities' (2012) de Jim Mansell y Julie Beadle-Brown.